Foreign Aid and Business Bottlenecks : A Study of Aid Effectiveness - Ferro, Esteban; Wilson, John S. (2012)
This paper proposes a new framework to analyze aid effectiveness. Using World Bank firm survey data and OECD aid flow data, the authors analyze whether aid targets areas that firms in developing countries have identified as obstacles for their growth and whether aid actually improves firms' perceptions of those areas. The analysis finds that aid does target the areas that firms have identified as obstacles; aid funding trade related projects is particularly effective in targeting the correct countries. For the most part, aid has a positive impact on improving firms' perceptions, particularly in the business environment. And for each target area, smaller aid disbursements tend to be more effective at improving firm perceptions than larger disbursements.